Improving tuberculosis case detection in underdeveloped multi-ethnic regions with high disease burden: a case study of integrated control program in China - Jun Li; Xiao-Qiu Liu; Shi-Wen Jiang; Xue Li; Fei Yu; Yan Wang; Yong Peng; Xiao-Ming Gu; Yan-Ni Sun; Hui Zhang; Li-Xia Wang (BMC, 2017)
Abstract Background In the underdeveloped multi-ethnic regions of China, high tuberculosis (TB) burden and regional inequity in access to healthcare service increase the challenge of achieving the End TB goals. Among all the provinces, the highest TB burden is reported in Xinjiang, where ethnic minorities and older people have suffered most. However, current case-finding strategy is inadequate given the complex social determinants and suboptimal case detection rates. Thus, we developed an integrated TB control program to improve case detection and conducted a pilot in Xinjiang from 2014 to 2015. In this case study, we summarized the activities and key findings. We also shared the experiences and challenges of implementing interventions and provided recommendations to inform the TB control program in the future. Case presentation The pilot interventions were implemented in one selected town in Yining based on local TB control programs. By applying tailor-made educational materials, outreach TB educational activities were conducted in diverse ways. In 22 Masjids, the trained imams promoted TB education to the Muslims, covering 20,440 person-times in 88 delivered preaching sessions. In seven schools, 1944 students were educated by the teachers and contributed to educating 6929 family members. In the village communities, 13,073 residents participated in household education and screening. Among them, 12,292 people aged under 65 years were investigated for suspicious pulmonary TB symptoms, where six TB patients were diagnosed out of 89 TB suspects; 781 older people were mobilized for screening directly by chest X-ray, where 10 patients were diagnosed out of 692 participants. Supportive healthcare system, multi-sectoral cooperation and multi-channel financing mechanism were the successful experiences of implementation. The interventions were proved to be more effective than the previous performance: the number of TB suspects consulting doctors and patients detected increased by 50% and 26%, respectively. The potential challenges, implications and recommendations should been taken into account for further program improvement. Conclusions In underdeveloped multi-ethnic regions with high TB burden, improving case detection is necessary and the interventions can be feasible and effective within a supportive system. More intensive educational and training approaches, a high index of TB suspicion and prioritization of older people in screening are recommended. To sustain and scale up the program, the impacts, cost-effectiveness, feasibility and acceptability of interventions warrant further research and evaluation in each specific context.